PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI ANDROID BERBASIS GOOGLE SITE UNTUK MENINGKATKAN PEMAHAMAN PROSES PEMBUATAN VIDEO PROFILE PADA MAHASISWA DKV UNIVERISITAS PGRI SILAMPARI - Aras Ade Gia; Apridona Surizka (Cattleya Darmaya Fortuna, 2023)
Development of learning media based on an Android application, how to make a video profile for students of the Visual Communication Design Department at UNPARI Lubuklinggau. The development of learning media on how to make a video profile is very appropriate to anticipate the limited learning resources for UNPARI DKV students. The benefit of this research is that with the learning media of Making a Video Profile, it is hoped that students will be more creative and straightforward in learning how to make a video. profile using cinematography techniques. This development will be designed using the Google Site and geyser application as the Android application. The research output target is the development of learning media for Video Profile Making to increase understanding of Cinematography among DKV UNPARI Lubuklinggau students